ANALISA PENDAPATAN USAHA MASYARKAT PADA PETERNAK AYAM BURAS DI KECAMATAN BINJAI KABUPATEN LANGKAT - Jailani, Binta Asshobari; Risdawati Br Ginting, (Journal of Innovation Research and Knowledge, 2024)
The aim of this research is to determine the income or level of profit and business feasibility in terms of the scale of free-range chicken rearing businesses in Binjai District, Langkat Regency. This research used a qualitative method with a descriptive analysis approach, which involved 3 breeders from 7 villages in Binjai District, Langkat Regency and were selected randomly. Research data was collected through in-depth interviews related to the research theme. The results of this research show that the analysis of the Jooper chicken farming business is very feasible to continue to be developed because it can increase income. From the R/C Ratio analysis, we get an average of 1.2. The analysis of the Elba chicken farming business is very feasible to continue with the R/C Ratio analysis getting 1.2. The analysis of the KUB chicken farming business is very feasible to continue with the R/C Ratio analysis of 1.4. Thus, the income of livestock businesses in Binjai District, Langkat Regency shows that there are business profits.